Popoin Media Based on Interactive Powerpoint for Primary Students' Dance Arts Education Practice - Putri, Farra Nabilla; Deasylina da Ary (LPPM Undiksha, 2024)
The implementation of learning is still not optimal in utilizing and using learning media so students' motivation and learning outcomes in learning still need to be higher. This research aims to develop POPOIN Media in an effort to improve learning outcomes in Floor Pattern Material for class V students. This research uses the Research and Development (R&D) method using the ADDIE development model. The subjects of this research are material experts and learning media experts. The test subjects were 27 fifth-grade students and fifth-grade elementary school teachers. The methods used to collect data are observation, interviews, questionnaires and test questions. The instruments used to collect data were questionnaire sheets and test questions. The techniques used to analyze data are qualitative and quantitative descriptive analysis and inferential statistics. The results of the research, namely POPOIN media on Floor Pattern material, received very good qualifications from experts so that it is suitable for use in learning. The results of the n-gain test data analysis show an increase in scores between the pretest and posttest. The results of the t-test show that there is a difference in the pretest and post-test scores. It was concluded that POPOIN media in Floor Pattern material could be used to improve students' dance learning outcomes.